Prone versus Supine Position for Lung Ultrasound in Neonates with Respiratory Distress - Louis, Deepak; Belen, Karen; Farooqui, Mansoor; Idiong, Nnanake; Amer, Reem; Hussain, Abrar; ElSayed, Yasser (American Journal of Perinatology, 2019)
Objective To study the feasibility of lung ultrasound (LUS) in prone position and to compare it with supine position in neonates with respiratory distress.Study Design Neonates ≥ 29 weeks of gestational age with respiratory distress requiring respiratory support within first 12 hours of life were enrolled prospectively. First LUS (fLUS) was done in the position infant was nursed (supine or prone), infant’s position changed, a second LUS (sLUS) was performed immediately and a third LUS (tLUS) was done 1 to 2 hours later. Primary outcome was the comparison of LUS scores (LUSsc) between fLUS and sLUS.Results Sixty-four neonates were enrolled. Common respiratory diagnoses were transient tachypnea of newborn (TTN; 53%) and respiratory distress syndrome (RDS; 41%). LUSsc was different between fLUS and sLUS (fLUSsc 6 [interquatile range: 4, 7] vs. sLUSsc 7 [4, 10], p < 0.001), while there was no difference between the fLUS and tLUS (fLUSsc 6 [4, 7] vs. tLUSsc 5 [3, 7], p = 0.43). Subgroup analysis confirmed similar findings in neonates with TTN, while in babies with RDS, all the three LUSsc were similar.Conclusion LUS is feasible in prone position in neonates. LUS scores were higher immediately after a change in position but were similar to baseline 1 hour after the change in position.
Keywords: lung ultrasound; supine; prone; neonate